80 Defunctioning Stomas the Answer to Avoid Anastomotic Leaks – Mere Precaution or A Necessity?. (4th May 2021) - Jayawardena, P; Peris, R; Hany, T
Abstract: Introduction: Anastomotic leaks account for one of the major complications following Colorectal Surgery. One of the surgical procedures to help avoid this complication include providing a defunctioning stoma. Evidence surrounding the provision of a defunctioning stoma has been supported extensively in the field of Colorectal Surgery. Method: A retrospective study was performed using a cohort of patients from a single teaching hospital between 2014 and 2019. 559 who had undergone elective bowel resection with primary anastomosis were identified and followed up. Data was captured using the hospital's electronic medical records; Quadramed and Evolve. Results: From the 559 patients 167 received a defunctioning stoma, out of which 114 were successfully reversed. 2 patients out of the 114 were deceased at 6 months following the reversal (p = 0.332). Furthermore, 15 patients of the 167 went on to develop complications at the anastomotic site (chi-square 25.37, p = <0.00001). 8 patients had anastomotic leaks and 9 patients developed strictures of which 2 patients developed both strictures and leaks. Conclusions: Although written literature points in favour of providing a defunctioning stoma; it is important to consider such a decision in a case-by-case manner, due to the complications involved instead of routinely providing a stoma as a prophylactic measure.